2 RECORDS OF THE GOVERNOR AND COMPANY OF THE MASSACHUSETTS BAY IN NEW ENGLAND 190 (Nathaniel B. Shurtleff ed., 1853) (enacted 1638) - (:unkn) unknown (General Publisher, 1638)
Military officers in every town shall appoint what arms are brought to public meetings. Also allowed officers to mandate safe disposure of ammuniation to prevent acquisition by an enemy.
--
Keywords: REGISTRATION